2014
DOI: 10.1016/j.ejpoleco.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The perfect finance minister: Whom to appoint as finance minister to balance the budget

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 72 publications
3
52
3
Order By: Relevance
“…). Political experience and party rank are crucial for ministerial efficiency in parliamentary democracies (Alexiadou ; Jochimsen & Thomasius ). Moreover, Europeans mostly overcame the economic crises of the 1980s and 1990s through political battles and alliances (Gourevitch ; Hall ).…”
Section: Introductionmentioning
confidence: 99%
“…). Political experience and party rank are crucial for ministerial efficiency in parliamentary democracies (Alexiadou ; Jochimsen & Thomasius ). Moreover, Europeans mostly overcame the economic crises of the 1980s and 1990s through political battles and alliances (Gourevitch ; Hall ).…”
Section: Introductionmentioning
confidence: 99%
“…Using data over the period 1960–2009, previous studies did not show that government ideology influenced deficits in the German states (Jochimsen and Nuscheler, ; Jochimsen and Thomasius, ). Other studies have shown evidence for ideology‐induced policies in the German states since the 1990s: rightwing governments hired more policemen than leftwing governments; rightwing governments were active in introducing tuition fees while leftwing governments abolished tuition fees; rightwing governments spent more on universities; rightwing governments promoted economic freedom (Kauder and Potrafke, ; Oberndorfer and Steiner, ; Potrafke, , ; Tepe and Vanhuysse, ).…”
Section: Resultsmentioning
confidence: 92%
“…Jochimsen and Nuscheler () and Jochimsen and Thomasius (), however, do not find partisan effects at the German state level.…”
mentioning
confidence: 88%